Professional development in an institution through the GROW model - Anisur Rahman, Md (Assyfa Learning Journal, 2023)
The teacher is a facilitator in helping the main character, namely students, achieve learning goals in class. In their professionalism as educators, teachers are expected to have abilities in material and teaching skills in conveying material so that students can understand it. The main aim of this research is to focus on the GROW model suitable for professional development in teaching styles. The GROW model consists of collaboration with Goals, Reality, Obstacles/Choices, and Will/Way Forward. This study will also focus on the demand for GROW coaching and the challenges of implementing the model in educational institutions. This is a research study based on literature and personal experience. Even though the GROW model is a new professional development process, it will be a more effective way of professional development if it is applied appropriately and constructively. Several issues and action plans must be adequately considered to implement this model. The researchers explain and introduce the GROW model and its impact on professional development with the help of literature and from the perspective of their practical experience.